Musikgeschichte im Überblick - Keil, Werner -1952 (Paderborn Brill | Fink, 2018)
The music history of Europe from antiquity to the 20th century in one clear volume. Epochs, genres, instruments and important composers are defined, explained and presented in a way suitable for study. This book provides students of music and musicology with an optimally structured overview of the central developments and trends in music history. The theory is illustrated by numerous illustrations and musical examples. References to further literature at the end of each chapter help with exam preparation and the consolidation of individual topics.
Keywords: Music history; Music education